2012
DOI: 10.1073/pnas.1212924109
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon dates from the Grotte du Renne and Saint-Césaire support a Neandertal origin for the Châtelperronian

Abstract: The transition from the Middle Paleolithic (MP) to Upper Paleolithic (UP) is marked by the replacement of late Neandertals by modern humans in Europe between 50,000 and 40,000 y ago. Châtelperronian (CP) artifact assemblages found in central France and northern Spain date to this time period. So far, it is the only such assemblage type that has yielded Neandertal remains directly associated with UP style artifacts. CP assemblages also include body ornaments, otherwise virtually unknown in the Neandertal world.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 38 publications
8
142
0
6
Order By: Relevance
“…The direct radiocarbon dating of the skeleton to 36,200 ± 750 14 C BP (OxA-18099; Hublin et al 2012a , that is, to 39.6-42.5 ka cal BP, has clarifi ed the picture in at least one way: under the assumption that the result is accurate, the dating unambiguously rejects the hypothesis that the St.-Césaire Neandertal is associated with the Mousterian component of EJOPsup. However, since the age range obtained overlaps the boundary between the chronostratigraphic time slots of the Châtelperronian and the Protoaurignacian in France, the dating does not reject that the skeleton relates to the latter instead of the former.…”
Section: St-césairementioning
confidence: 90%
See 3 more Smart Citations
“…The direct radiocarbon dating of the skeleton to 36,200 ± 750 14 C BP (OxA-18099; Hublin et al 2012a , that is, to 39.6-42.5 ka cal BP, has clarifi ed the picture in at least one way: under the assumption that the result is accurate, the dating unambiguously rejects the hypothesis that the St.-Césaire Neandertal is associated with the Mousterian component of EJOPsup. However, since the age range obtained overlaps the boundary between the chronostratigraphic time slots of the Châtelperronian and the Protoaurignacian in France, the dating does not reject that the skeleton relates to the latter instead of the former.…”
Section: St-césairementioning
confidence: 90%
“…Where the western part is concerned, however, Hublin et al ( 2012a ) This claim is unsupported, as shown by Banks et al's ( 2013 ) Bayesian modeling of the chronology of the Protoaurignacian. The oldest of the lower limits of these authors' 95.4 % confi dence intervals for Isturitz's modeled cal BP results is 41,840, and the corresponding youngest upper limit is 40,078; both are fully consistent with the 39.9-41.5 ka cal BP range modeled for the entire technocomplex.…”
Section: Protoaurignacianmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, two 14 C-AMS dates were obtained on bone samples from the newly discovered Tolbor 21 site , Gladyshev et al, 2013. Samples were selected for dating when showing a satisfying amount of collagen yield (>1%) (Ambrose, 1990,Weber et al, 2005Hublin et al, 2012) and C:N between 2.9 and 3.5 (Klinken, 1999). The samples were pretreated at MPI-EVA Leipzig using the method described in Talamo and Richards (2011).…”
Section: Chronologymentioning
confidence: 99%